Dual-tasking interference is exacerbated outdoors: A pilot study - Almajid, Rania; Appiah-Kubi, Kwadwo O.; Cipriani, Daniel; Goel, Rahul (Frontiers in Sports and Active Living, 2023)
Walking while texting can create gait disturbances that may increase fall risk outdoors compared to indoors environment. To date, no study has quantified the effect of texting on motor behavior using different dynamic tasks in outdoor environments. We aimed to explore the impact of texting on dynamic tasks in indoor and outdoor environments. Twenty participants (age 38.3 ± 12.5 years, 12 F) had a Delsys inertial sensor fixed on their back and completed walk, turn, sit-to-stand, and stand-to-sit subtasks with and without texting in both indoor and outdoor environments. While there was no difference in texting accuracy (p=0.3), there was a higher dual-tasking cost in walking time with texting outdoors than indoors (p=0.008). Dual tasking has a greater impact on walking time outdoors compared to an indoor environment. Our findings highlight the importance of patient education concerning dual-tasking and pedestrian safety in clinical settings.